3D simulations for wireless ad hoc networks in grid environment - Filiposka, Sonja; Trajanov, Dimitar (My University, 2010)
In this paper the usage of grid environment for fast simulation of wireless ad hoc networks in 3D terrains is presented. The possibilities and gains of the grid environment have proven to be very resourceful when simulating wireless ad hoc networks using the NS-2 simulator especially when considering lengthy simulations for performance evaluation with a heavy traffic load involving computing intensive calculations like the estimation of received power in a 3D environment based on the radio wave diffraction.
Keywords: wireless mobile ad hoc networks, network simulator, Durkin’s radio propagation model, performance evaluation, grid environment